1984
DOI: 10.1128/aem.47.1.193-194.1984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of butanol on lipid composition and fluidity of Clostridium acetobutylicum ATCC 824

Abstract: Butanol, at sub-growth-inhibitory levels, caused a ca. 20 to 30% increase in fluidity of lipid dispersions from Clostridium acetobutylicum. When grown in the presence of butanol or into stationary phase, C. acetobutylicum synthesized increased levels of saturated acyl chains at the expense of unsaturated chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 6 publications
3
60
0
1
Order By: Relevance
“…Production of cyclopropane fatty acids also coincides with solvent production (Lepage et al, 1987;Vollherbst-Schneck et al, 1984;Zhao et al, 2003), but overexpression of the cyclopropane fatty acid synthesis gene cfa (CAC0877) reduces solvent production (Zhao et al, 2003). In E. coli, acetate treatment induces cfa expression (Arnold et al, 2001), and deletion increases acid-stress sensitivity (Chang and Cronan, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of cyclopropane fatty acids also coincides with solvent production (Lepage et al, 1987;Vollherbst-Schneck et al, 1984;Zhao et al, 2003), but overexpression of the cyclopropane fatty acid synthesis gene cfa (CAC0877) reduces solvent production (Zhao et al, 2003). In E. coli, acetate treatment induces cfa expression (Arnold et al, 2001), and deletion increases acid-stress sensitivity (Chang and Cronan, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, butanol is also toxic and has been shown to disrupt transmembrane DpH and Dc, lower intracellular ATP levels, and inhibit glucose uptake (Bowles and Ellefson, 1985;Huang et al, 1985;Terracciano and Kashket, 1986). During solventogenesis, clostridia increase saturated fatty acid chain content (Baer et al, 1987;Lepage et al, 1987;Vollherbst-Schneck et al, 1984;Zhao et al, 2003) to modulate their membrane fluidity in the presence of solvents (Baer et al, 1989;Vollherbst-Schneck et al, 1984), a process known as homeoviscous adaptation (Sinensky, 1974). Solventogenic-phase and butanol-stressed clostridia also express stress genes, including all major chaperones Bahl et al, 1995;Pich et al, 1990;Schaffer et al, 2002;Terracciano et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Total lipids in C. acetobutylicum have been found to account for 5-6% of the dry cell weight (Lepage et al, 1987). It has been also reported that solvent exposure leads to an increase in the ratio of saturated and cyclopropane fatty acids to unsaturated membrane fatty acids (Baer et al, 1987;Vollherbst-Schneck et al, 1984;Zhao et al, 2003), changes in the mean fatty acid acyl chain length (Lepage et al, 1987;Vollherbst-Schneck et al, 1984;Zhao et al, 2003) and changes in the membrane phospholipid composition (Johnston and Goldfine, 1992;Lepage et al, 1987;MacDonald and Goldfine, 1991). Nevertheless, due to the absence of specific compositional information about these changes, a single lipid biosynthesis equation (see Supplementary Appendix 1) was used in the calculation of biomass composition over the entire course of exponential growth.…”
Section: Representation Of Lipid Biosynthesismentioning
confidence: 99%
“…Hydrophobic metabolic endproducts such as butanol, acetone and organic acids rapidly partition into the lipid membrane [26,27]. At high concentrations, these compounds may disrupt the membrane structure and inhibit bacterial growth [28][29][30]. Organic acids such as acetate and lactate are excreted passively in some bacteria and carrier-mediated in others [31].…”
Section: Passive Diffusionmentioning
confidence: 99%